2018
DOI: 10.3390/ijms19051514
|View full text |Cite
|
Sign up to set email alerts
|

Jatrorrhizine Hydrochloride Suppresses Proliferation, Migration, and Secretion of Synoviocytes In Vitro and Ameliorates Rat Models of Rheumatoid Arthritis In Vivo

Abstract: Jatrorrhizine hydrochloride (JH), an active component isolated from the traditional Chinese herb Coptis chinensis, has been reported to have antimicrobial, antitumor, antihypercholesterolemic, and neuroprotective activities. However, its antirheumatoid arthritis (RA) property remains unknown. In this study, a collagen-induced arthritis (CIA) rat model was used to evaluate the therapeutic effects of JH on RA by using arthritis score, radiological evaluation, and histopathological assessment. The in vitro effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Palmatine displays anti-inflammatory function by inhibiting TRIF-dependent NF-κB ( Yan et al., 2017 ). Jatrorrhizine suppresses proliferation, migration, and secretion of synoviocytes in an animal model with rheumatoid arthritis ( Qiu et al., 2018 ). Baicalein exerts anti-inflammatory function by inhibiting NF-κB transactivation ( Patwardhan et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Palmatine displays anti-inflammatory function by inhibiting TRIF-dependent NF-κB ( Yan et al., 2017 ). Jatrorrhizine suppresses proliferation, migration, and secretion of synoviocytes in an animal model with rheumatoid arthritis ( Qiu et al., 2018 ). Baicalein exerts anti-inflammatory function by inhibiting NF-κB transactivation ( Patwardhan et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, JH did not affect JNK and NF-κB signaling pathways, however, it could significantly suppress the phosphorylation levels of RANKL-mediated p38 and ERK. Interestingly, our previous study showed that, in synoviocyte cell line MH7A, JH also significantly inhibited TNFα-induced p38 and ERK activation [ 23 ]. Thus, it is possible that blocking p38 and ERK activation might be an important active site of JH.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to our knowledge, no study has investigated its anti-osteoclastogenic and anti-resorptive actions. In our recently published paper, JH has been demonstrated to inhibit focal bone erosion in collagen-induced arthritis (CIA) rat model [ 23 ]. As osteoclast is the sole cell type responsible for bone resorption, therefore, we speculated that JH may have a potential therapeutic role of anti-osteolytic diseases through inhibiting osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…We searched the literature related to the pharmacological mechanism of these 13 active ingredients. Encouragingly, the literature shows that 12 active ingredients could exert anti-inflammatory effects by inhibiting the NF-κB signaling pathway (Sun et al, 2015b; Li et al, 2016b; Wang et al, 2016b; Yan et al, 2017; Chen et al, 2017a; Chen et al, 2017b; Chen et al, 2018; Guo et al, 2018; Qiu et al, 2018; Lu et al, 2019; Luan et al, 2019; Pan et al, 2019), while only 8 active components exert antioxidant effects by activating the Nrf2 signaling pathway (Li et al, 2016a; Chen et al, 2018; Fang et al, 2018; Luo et al, 2018; Wang et al, 2018; Chen et al, 2019; Jia et al, 2019; Jiang et al, 2019) ( Figure 11 ). Besides, there are six active ingredients that exert mucosal protective effects by restoring tight junction protein expression (Zhu et al, 2012; Bribi et al, 2016; Ruan et al, 2016; Chen et al, 2017a; Peng et al, 2018; Yu et al, 2018) ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%